D-Dimer Levels of COVID-19 patients with Diabetes Mellitus: a Retrospective study - Dharma Lindarto; Ginting, Fransiscus (TALENTA Publisher, Universitas Sumatera Utara, 2023)
Background: Diabetes is the commonest comorbidity in Coronavirus disease 2019 (COVID-19) patients, and D-dimer level assessment has reliable parameters for assessing and evaluating the prognosis of COVID-19 patients with comorbid. This study aims to compare D-dimer, FPG, and PPG levels between COVID-19 patients with comorbid. Method: We conducted a retrospective descriptive and analytical study carried out at D-dimer, FPG, and PPG levels of COVID-19 patients with comorbid in a tertiary Hospital in Medan, Indonesia, from April 04, 2020, to November 22, 2020. The data were collected by cheek list, using electronic medical records. The data included age, gender, medical history, comorbidity disease inward, and ICU admission. All these cases of COVID-19 have been confirmed in the laboratory by Real-Time Reverse Transcription Polymerase Chain Reaction (RT-PCR). Result: From 323 COVID-19 patients with comorbidities, there are significant differences in D-dimer, FPG, and PPG levels between all groups of COVID-19 patients with the comorbid disease (p<0.05), and there is a significant difference in D-dimer, FPG, and PPG level between severity of COVID-19 with comorbidities (p<0.005). Conclusion: There is a significant difference between D-dimer, FPG, and PPG levels in COVID-19 patients with comorbidities in comorbid type and severity of COVID-19.